National culture and comparative industrial relations theory - Black, Boyd (Belfast, 2002)
"This paper develops a cultural model of comparative industrial relations theory that will explain the cross-national pattern of industrial relations institutions and any change in this over time. A critical review of the existing body of theory establishes that national culture is currently given little weight as an explanatory variable. A cultural model is developed, based on a definition and specification of culture developed by Hofstede. Industrial relations variables are regressed on Hofstede's cultural indices. National culture is found to be significantly associated with all the dimensions of industrial relations. A related cultural model is developed to explain longitudinal change in industrial relations institutions and outcomes."